2020
DOI: 10.1038/s41591-020-0761-3
|View full text |Cite
|
Sign up to set email alerts
|

Viable bacterial colonization is highly limited in the human intestine in utero

Abstract: Mucosal immunity develops in the human fetal intestine by 11–14 weeks gestation, yet whether viable microbes exist in utero and interact with the intestinal immune system is unknown. Bacterial-like morphology was identified in pockets of human fetal meconium at mid-gestation by scanning electron microscopy (n=4) and a sparse bacterial signal was detected by 16S rRNA sequencing (n=40 of 50) compared to environmental controls (n=87). Eighteen taxa were enriched in fetal meconium with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
210
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 214 publications
(217 citation statements)
references
References 66 publications
5
210
0
2
Order By: Relevance
“…Finally, to confirm that first-trimester HBCs have microbicidal capacity, we cultured HBCs with Lactobacillus crispatus (a microbe reported to be found in very low abundance within the second trimester fetal intestine; Rackaityte et al, 2020 ) and E. coli (not found in the fetus; Rackaityte et al, 2020 ). We find that HBC are as efficient as PAMM1a at killing both L. crispatus and E. coli when cultured at a multiplicity of infection (MOI) of 1 ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Finally, to confirm that first-trimester HBCs have microbicidal capacity, we cultured HBCs with Lactobacillus crispatus (a microbe reported to be found in very low abundance within the second trimester fetal intestine; Rackaityte et al, 2020 ) and E. coli (not found in the fetus; Rackaityte et al, 2020 ). We find that HBC are as efficient as PAMM1a at killing both L. crispatus and E. coli when cultured at a multiplicity of infection (MOI) of 1 ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…We recently reported that bacteria are variably present in the fetal intestine through high resolution scanning electron microscopy, sequencing, and viable isolation methods. The presence of Micrococcus luteus in fetal meconium was correlated with a higher proportion of intestinal PLZF + CD161 + memory T cells and limited their ability to produce IFNγ as compared to non-fetal M. luteus species (101). This finding is supported by a study that demonstrated the requirement of a microbiome for the development of PLZF + T cells in mice (139).…”
Section: In Utero Environment Contributes To the Regulation Of Fetalmentioning
confidence: 60%
“…Production of IFNγ by fetal T cells may be limited by intestinal macrophages expressing high levels of LLT1, the natural ligand of CD161 (29). Exposure to fetal-specific M. luteus induces LLT1 on fetal antigen presenting cells (101), suggesting that commensal fetal bacteria may modulate this axis to promote intestinal immune tolerance. Further, suppressive functions of intestinal macrophages are well-described in adults (102)(103)(104) and it is likely that similar mechanisms are also employed by the fetal immune system.…”
Section: Cell-extrinsic Mechanismsmentioning
confidence: 99%
“…This has led to discussion in the literature on the caveats associated with studies of the microbiota of very low microbial biomass, or potentially sterile, body sites (4754). In particular, there has been much debate over the existence of a placental microbiota (3145, 50, 5569) and of in utero microbial colonization of the human fetus (36, 4446, 64, 7072).…”
Section: Introductionmentioning
confidence: 99%
“…Fifth, the taxonomic data of the detected bacteria should be ecologically plausible (50, 62). There have been many studies that may have met one or two of these criteria (3146, 7880), but no study has yet attempted to simultaneously meet all criteria and ultimately conclude that there is widespread colonization of the placenta and/or fetus by viable microbial communities (72).…”
Section: Introductionmentioning
confidence: 99%